Genetic Testing in Familial Hypercholesterolemia: Is It for Everyone? - Medeiros, Ana Margarida (2023)
Purpose of Review: Lipid measurements and genetic testing are the main diagnostic tools for FH screening that are available in many countries. A lipid profile is widely accessible, and genetic testing, although available worldwide, in some countries is only performed in a research context. Still FH is diagnosed late, showing lack of early screening programs worldwide. Recent Findings: Pediatric screening of FH was recently recognized by the European Commission Public Health Best Practice Portal as one on the best practices in non-communicable disease prevention. The early diagnosis of FH and the lowering of LDL-C values over lifespan can reduce the risk of coronary artery disease and offer health and socioeconomic gains. Summary: Current knowledge about FH shows that early detection through appropriate screening needs to become a priority in healthcare systems worldwide. Governmental programs for FH identification should be implemented to unify the diagnosis and increase patient identification.